Infeksi Alami Canine Parvovirus pada Anjing Kintamani di Desa Sukawana, Kintamani, Bangli, Bali (NATURAL INFECTION OF CANINE PARVOVIRUS IN KINTAMANI DOGS OF SUKAWANA VILLAGE, KINTAMANI, BANGLI, BALI) - Suartini, I Gusti Ayu Agung; Sendow, Indrawati; Suarsana, I Nyoman; Setiasih, Ni Luh Eka; Janah, Maratun (Jurnal Veteriner; Vol 20 No 2 (2019)DO - 10.19087/jveteriner.2019.20.2.234, 2019)
Kintamani  dog as one of germ plasm owned by Bali province has been widely accepted as dog of Indonesian origin which need to be preserved.  Report have shown that puppies of Kintamani dogs sold in Denpasar animal market often die due to Canine parvovirus (CPV) infection.  The mortality of CPV infection in puppies can reach as high as 91% espescially in unvaccinated dogs. As the mortality of CPV in dogs is very high, it is important to find out the seroprevalence of CPV infection in Kintamani dogs in Sukawana village.  Up to now, the seroprevalence of CPV infection in Sukawana, the natural habitate of Kintamani dog has never been reported.  In this study the sample collection and area selection was conducted by haemaggutination inhibition (HI) test.  Sera sample were concluded positive if the HI titers of sera were > 64 HI units.  Seroprevalence of CPV infection was calculated by dividing the number of positive sera with the total sera samples. The seroprevalence of CPV among dogs was determined using non parametric analysis (Chi-Square). From 70 sera samples collected 67.1% (47/70) were antibody positive against CPV. The highest seroprevalence was found in Banjar Sukawana 22.8% (16/70). A higher seroprevalence was found in female dogs 45.7% (32/70) compare to male dogs 21.4% (15/70). Kintamani dogs aged between 724 month have the highest seroprevalence 27.1% (19/70). Based on the distribution of antibody titers, the seroprevalence antibody >64 HI was 65.7%. The result showed that the high titer (> 64 HI) of antibody against CPV, it was shown that CPV infection has occurs naturally in kintamani dog at Sukawana village.